Petrologia dos topázio riólito pórfiro e topázio granito pórfiro do morro Bom Futuro, mina Bom Futuro, Rondônia - Ciotta, Matheus Ramos (2019)
The Bom Futuro mine has the second largest tin reserve and production in Brazil, with about 192,000 tons produced since its discovery in 1987. The mine is located in the county of Ariquemes, north-central region of Rondonia State, and brings together two adjacent hills called Bom Futuro and Palanqueta and adjacent planed areas. The main primary mining front is located in the Bom Futuro hill, where are recognized gnaisses and amphibolites from the basement, syenite and trachyte dykes, pipe breccias, topaz rhyolite porphyry and topaz granite porphyry dykes, staniferous pegmatite lenses and quartz veins, and later quartz, calcite, fluorite and sulphide veinlets. Topaz granitic porphyry (topaz rhyolite porphyry and topaz granite porphyry) and syenitic porphyry are included, respectively, in the late subalcaline/peraluminous and alkaline/peralcaline subsuites of the Intrusive Suite Younger Granites of Rondonia (998 - 974 Ma). In the Bom Futuro Hill, contact relations define a temporal sequence between porphyry: syenitic porphyry, topaz rhyolite porphyry and topaz granite porphyry. The topaz rhyolite porphyry occurs as ring dikes, with diferente thicknesses (<10 m) and attitudes in the eastern and northern portions of the hill. Contact with host rocks is abrupt, sometimes with breccias in both endocontact and exocontact. Topaz granite porphyry cut all the remain lithologies in the hill, except for pegmatites and quartz veins of the second phase and later veinlets. The topaz granite porphyry occurs as ring and radial dikes, with abrupt contact with the host rocks, sometimes with breccias, and locally, contain subhorizontal pegmatites (stockscheider) and endogreisen pockets. The topaz granitic porphyry are leucocratic and porphyritic in texture, with quartz and microcline phenocrystals showing snowball texture and albite, in fine to very fine grained matrix composed essentially of the same minerals besides topaz, Li-mica and fluorite. Sulphide aggregates (pyrite, sphalerite and galena) of a few centimeters locally give a mottled appearance to the rock. Geochemically, topaz granitic porphyry are peraluminous rocks and have characteristics of A-type granites, within plate, highly differentiated and rare-metal granites. Topaz granitic porphyry have weak to nonexistent LREE enrichment over HREE and moderate negative europium anomaly. Topaz granite porphyry presents characteristics that suggest a greater differentiation from topaz rhyolite. The genesis of these porphyries is due to the combination of magmatic (eg fractional crystallization) and hydrothermal processes.